The von Willebrand Pig as a Model for Atherosclerosis Research - Fuster, V; Bowie, E J W (Thrombosis and Haemostasis, 1978)
In order to evaluate a possible role played by platelets in the development of atherosclerosis, the aortas of 11 control pigs and 11 homozygous von Willebrand (vWd) pigs were examined for spontaneous atherosclerosis. Of the 11 normal pigs, 6 showed multiple atherosclerotic plaques with an intimal thickening of 63 to 130 μm. In contrast, none of the von Willebrand pigs had multiple plaques and only one showed a single lesion of more than 2 mm in diameter.In a prospective study 5 control pigs and 5 vWd pigs were given a high (2%) cholesterol diet from the age of 3 to 9 months. All of the controls developed atherosclerotic plaques. In 4 of the pigs the plaques exceeded 13% of the aortic surface with an intimal thickening of 50 to 390 pm. In contrast, only one of the vWd pigs developed atherosclerotic plaques which only involved 7% of the aortic surface. Most of the vWd pigs, however, developed non-atherosclerotic flat fatty lesions. These findings may be related to the imp aired platelet arterial wall interaction in vWd. The vWd pigs seem to be an ideal model for atherosclerosis research.